1981
DOI: 10.1128/aac.19.4.593
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Campylobacter jejuni with special reference to resistance patterns of Canadian isolates

Abstract: Agar dilution antimicrobial susceptibility testing of Camphylobacter jejuni showed that erythromycin, clindamycin, nitrofurantoin, and gentamicin were the most active compounds, inhibiting 90% of the isolates at a concentration of 1 ,tg/ ml or less. The frequency of high-level erythromycin resistance was 1%. Erythromycin-resistant isolates showed cross-resistance to clindamycin. All strains were inhibited by chloramphenicol at -8,ig/ml. About 20% of the isolates were resistant to tetracycline at 4 ,ug/ml. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
55
4
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 16 publications
3
55
4
2
Order By: Relevance
“…We used a twotimes-higher concentration of polymyxin B (100,00 IU/liter) than that suggested by Karmali et al (8,9), but our results indicate that the addition of polymyxin B to mCCDA at this concentration does not inhibit the growth of either the C. jejuni or the C. coli strains tested in this study.…”
contrasting
confidence: 40%
See 2 more Smart Citations
“…We used a twotimes-higher concentration of polymyxin B (100,00 IU/liter) than that suggested by Karmali et al (8,9), but our results indicate that the addition of polymyxin B to mCCDA at this concentration does not inhibit the growth of either the C. jejuni or the C. coli strains tested in this study.…”
contrasting
confidence: 40%
“…The antibiotic is bactericidal for Gram-negative bacteria, and its mode of action comprises two major steps, permeabilization of the outer membrane and induction of lethal leakage of cytoplasmic components (16). Although Karmali et al (8,9) reported that a high concentration of polymyxin B (50,000 IU/liter) improved the selectivity of media for the primary isolation of Campylobacter jejuni, the agent has not been used at high concentrations in recent times because Campylobacter coli was found to be highly susceptible when the agent was added to media such as Mueller-Hinton (MH) agar and Preston enrichment media (5,7,11). Polymyxin B has not been used at high concentrations in selective media containing a combination of cefoperazone and activated charcoal, such as mCCDA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in the United States, 3% of C. jejuni strains were resistant to erythromycin, but a much greater incidence was noted among C. coli isolates, with 70% of isolates from hogs found to be resistant (13). Others have also noted a greater prevalence of erythromycin-resistant strains among C. coli than among C. jejuni isolates (3,6). In a recent Centers for Disease Control survey, 2.4% of Campylobacter strains were found to be resistant to erythromycin (10).…”
mentioning
confidence: 99%
“…Erythromycin is the drug of choice for the treatment of serious cases of campylobacter gastroenteritis. The incidence of isolation of erythromycinresistant campylobacter strains ranges from less than 1% in Canada and the United Kingdom (9,22,41) to 8.4% in Belgium and 10% in Sweden (46,47). In the United States, Wang et al reported that 3% of campylobacter strains from human sources were resistant to erythromycin (48).…”
mentioning
confidence: 99%